The Effectiveness of Modern Dressings in Healing Diabetic Ulcers in the Poly Surgery at Bhayangkara Hospital Balikpapan - Andi Adli; Marina Kristi Layun (Ammar Dharma Foundation, 2025)
Background: Diabetic ulcers are a form of chronic complications of diabetes mellitus in the form of open wounds on the surface of the skin, which can be accompanied by local tissue death, damage to skin tissue starting from the epidermis, dermis, subcutaneous tissue and can spread to deeper tissues, such as bone. And muscles. Management that can be used to treat diabetic ulcers consists of pharmacological and non pharmacological management. One of the interventions that can be given to treat diabetic ulcers non-pharmacologically is by carrying out modern dressing treatments.Objective: This study aimed to determine the differences in wound conditions before and after treatment using modern dressing techniques in patients with diabetic ulcers.Methods: This study was pre-experimental with a one-group pre and post-test design approach. The sample in the study consisted of 15 respondents using the Accidental Sampling technique. Data was collected in the Poly Surgery at Bhayangkara Hospital using the BWAT observation sheet (Bates Jensen Wound Assessment Tool) from 1 May 2023 to 1 June 2023. The data analysis used was the Wilcoxon Test.Results: Research on wound conditions before and after treatment using modern dressing techniques in patients with diabetic ulcers obtained a P value of 0.005.Conclusion: The results of the Wilcoxon test calculation indicate it is effective in using modern dressing techniques in diabetic ulcer patients in the Poly Surgery at Bhayangkara Hospital. The recommendation for this research is that it can be a reference for students and nursing staff to use modern dressings in modern wound care.